Aplikasi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Guru di Madrasah Aliyah Negeri Makale Kabupaten Tana Toraja - Tri Karyanto (IAIN PAREPARE, 2021)
This study aims (1) to find out the description of the leadership characteristics of the Madrasah Aliyah Head of Makale Negeri Tana Toraja Regency, (2) to find out the description of the competency of Madrasah Aliyah Negeri Makale teachers in the Tana Toraja District, and (3) to find out the principal's leadership application in improving teacher competency in Madrasah Aliyah Negeri Makale, Tana Toraja Regency. This research was classified as a qualitative descriptive study. The research subjects in this study amounted to 39 people consisting of educators and education staff. Data collection in this study uses observation, documentation, questionnaires, and interviews. Data collected were analyzed using descriptive analysis techniques supplemented with frequency distribution tables. The results showed that (1) the leadership of the Makale MAN head of Tana Toraja Regency was democratic and authoritarian. This was evident from the various treatments and policies issued by the Makale MAN head of Tana Toraja Regency as the leader of teachers and employees as subordinates, (2) the competence of MAN teachers The Makale of Tana Toraja Regency is included in the good category seen from various aspects of competency assessment on pedagogical, social, personal and professional competencies, based on indicators of teacher competency assessment guidelines for the ministry of national education, and (3) the leadership characteristics of MAN Makale Tana Toraja Regency has been applied in an effort to improve teacher competence well, this can be seen from the implementation of various madrasa head policies based on democratic leadership but in certain cases leaders apply the authoritarian leadership nature which aims to maintain a conducive work climate and the professionalism of the work of their subordinates in MAN Makale Tana Toraja Regency. Through the application of the leadership characteristics of the madrasa head proven to be able to improve teacher competence in MAN Makale Tana Toraja Regency